Analysis of the Effect of Leadership, Motivation and Compensation on Employee Performance (Case Study at BPRS Bumi Artha Sampang) - Setyanugraha, Muhammad; Dahlan, Ahmad (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The purpose of this research is to find out that an organization or company is able to influence leadership style, work motivation and kompensasi on employee development at Sharia Rural Bank (BPRS) Bumi Arta Sampang so that it can provide changes about progress and opportunities for each employee to advance to a higher and more level. well so as to achieve a success. This research uses quantitative research methods. The sample used is all employees at BPRS Bumi Arta Sampang. Based on the results of this thesis research, it is necessary to remember the importance of the influence of work motivation leadership style and kompensasi on employee development in the work process at BPRS Bumi Arta Sampang. From the achievements obtained at BPRS Bumi Arta Sampang, there are ups and downs in the average achievement of marketing officers including savings, credit and deposits so that the company is unable to reach the target in 2020.